Blended e-learning and certification for medicines development professionals: results of a 7-year collaboration between King’s College, London and the GMDP Academy, New York - Silva, Honorio; Stonier, Peter; Chopra, Pravin; Coots, Jacob; Criscuolo, Domenico; Guptha, Soneil; Jones, Stuart; Kerpel-Fronius, Sandor; Kesselring, Gustavo; Luria, Xavier; Morgan, David; Power, Eddie; et al. (Frontiers in Pharmacology, 2024)
The field of Medicines Development faces a continuous need for educational evolution to match the interdisciplinary and global nature of the pharmaceutical industry. This paper discusses the outcomes of a seven-year collaboration between King's College London and the Global Medicines Development Professionals (GMDP) Academy, which aimed to address this need through a blended e-learning program.The collaboration developed a comprehensive curriculum based on the PharmaTrain syllabus, delivered through a combination of asynchronous and synchronous e-learning methods. The program targeted a diverse range of professionals serving in areas related to Medical Affairs, Results: Over seven annual cohorts, 682 participants from eighty-six countries were enrolled in the program. The program's effectiveness was assessed using Kirkpatrick's model, showing elevated levels of satisfaction (over 4.0 on a five-point scale), suggesting significant gains in competence at the cognitive level and leveraged performance. Notably, 70% of responding alumni reported significant improvement in their functions, corroborated by 30% of their supervisors. The further long-term impact of the program on their respective organization has not been established.The GMDP Academy's program has significantly contributed to life-long learning in Medicines Development, addressing educational gaps and fostering interdisciplinary collaboration. Its success highlights the importance of continuous education in keeping pace with the industry's evolving demands and underscores the potential of blended learning in achieving educational objectives in pharmaceutical medicine.